Slaying (Yet Again) the Brain-Eating Zombie Called the “Isochore Theory”: A Segmentation Algorithm Used to “Confirm” the Existence of Isochores Creates “Isochores” Where None Exist - Graur, Dan (International journal of molecular sciences, 2022)
The isochore theory, which was proposed more than 40 years ago, depicts the mammalian genome as a mosaic of long, homogeneous regions that are characterized by their guanine and cytosine (GC) content. The human genome, for instance, was claimed to consist of five compositionally distinct isochore families. The isochore theory, in all its reincarnations, has been repeatedly falsified in the literature, yet isochore proponents have persistently resurrected it by either redefining isochores or by proposing alternative means of testing the theory. Here, I deal with the latest attempt to salvage this seemingly immortal zombie—a sequence segmentation method called isoSegmenter, which was claimed to “identify” isochores while at the same time disregarding the main characteristic attribute of isochores—compositional homogeneity. I used a series of controlled, randomly generated simulated sequences as a benchmark to study the performance of isoSegmenter. The main advantage of using simulated sequences is that, unlike real data, the exact start and stop point of any isochore or homogeneous compositional domain is known. Based on three key performance metrics—sensitivity, precision, and Jaccard similarity index—isoSegmenter was found to be vastly inferior to isoPlotter, a segmentation algorithm with no user input. Moreover, isoSegmenter identified isochores where none exist and failed to identify compositionally homogeneous sequences that were shorter than 100−200 kb. Will this zillionth refutation of “isochores” ensure a final and permanent entombment of the isochore theory? This author is not holding his breath.